Conopeptide-functionalized nanoparticles selectively antagonize extrasynaptic N‑methyl‑D‑aspartate receptors and protect hippocampal neurons from excitotoxicity in vitro - Valente, Pierluigi; Kiryushko, Darya; Sacchetti, Silvio; Machado, Pedro; Cobley, Claire; Mangini, Vicenzo; Porter, Alexandra E.; Spatz, Joachim P.; Fleck, Roland A.; Benfenati, Fabio; Fiammengo, Roberto (ACS nano, 2020)
Autor: Valente, Pierluigi et al.; Genre: Zeitschriftenartikel; Im Druck veröffentlicht: 2020-06-23; Keywords: Abt. Spatz; Titel: Conopeptide-Functionalized Nanoparticles Selectively Antagonize Extrasynaptic N‑Methyl‑D‑aspartate Receptors and Protect Hippocampal Neurons from Excitotoxicity In Vitro
Gesehen am 21.08.2020